Stagnation point heat flux measurements in a plasma wind tunnel using a diamond heat transfer gauge - Penty Geraets, R; McGilvray, M; Loehle, S; Hufgard, F (American Institute of Aeronautics and Astronautics, 2019)
A Diamond Heat Transfer Gauge has been used to measure the stagnation point heat flux at three flow conditions in an arc heated plasma wind tunnel. The gauge was coated with a thin layer of copper to provide a known surface catalycity and reflectivity. The temperature dependent impulse response of the probe was determined from a finite element model of the probe, and from the result of a laser-based calibration experiment using the Non-Integer System Identification method. The two sets of impulse responses were used to calculate heat flux from a measured temperature rise in the wind tunnel. Differences between the impulse responses from the two methods, particularly at higher initial temperatures, led to differences in measured heat fluxes of up to 55 %. A measurement taken using a steady state calorimeter gauge did not conclusively agree with heat flux measurements calculated using impulse responses from either method.